2023
DOI: 10.7759/cureus.33581
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the COVID-19 Lockdown on the Frequency of Acute Poisoning Presentation to Adult and Pediatric Emergency Departments

Abstract: Background The coronavirus type 2 that causes severe acute respiratory syndrome (SARS-CoV-2) was detected in December 2019 in Wuhan, China. A worldwide emergency response has been initiated because of the fast rise in the number of cases and fatalities during the early stages of the pandemic when vaccinations and efficient medical care were unavailable. Misinformation spread quickly in the early phases of the pandemic, leading to the inappropriate use of medications, chemicals, and traditional remed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Likewise, the senior age group showed a stable percent through the studied years. Alhussein et al, 2023 recorded similar findings in their study covering the period of the pandemic. For adolescents, there's a noticeable decrease from 12.26% in 2019 to 10.75% in 2020, 11.23% in 2021 and finally 9.48% in 2022.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Likewise, the senior age group showed a stable percent through the studied years. Alhussein et al, 2023 recorded similar findings in their study covering the period of the pandemic. For adolescents, there's a noticeable decrease from 12.26% in 2019 to 10.75% in 2020, 11.23% in 2021 and finally 9.48% in 2022.…”
Section: Discussionsupporting
confidence: 68%
“…Changes were also observed in food productrelated toxicities, which declined in 2020 and 2021, then rebounded to pre-pandemic levels in 2022. This could be attributed to the shift in dietary habits towards home cooking during the pandemic, followed by a return to consuming meals outside of home pre-and post-pandemic (Peden et al, 2008;Alhussein et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has also changed the trend of hospitalizations related to poisoning as well as deaths related to poisonings 5 , 6 . For instance, Hadeiy et al found a higher rate of alcohol intoxication and intoxication-related mortality during the COVID-19 pandemic compared to before 7 .…”
Section: Introductionmentioning
confidence: 99%